Self-Mixing Interferometer for Acoustic Measurements through Vibrometric Calibration - Simon Chanu-Rigaldies; Pierre Lecomte; Sébastien Ollivier; Thomas Castelain (Sensors, 2024)
The Self-Mixing Interformeter (SMI) is a self-aligned optical interferometer which has been used for acoustic wave sensing in air through the acousto-optic effect. This paper presents how to use a SMI for the measurement of Sound Pressure Level (SPL) in acoustic waveguides. To achieve this, the SMI is first calibrated in situ as a vibrometer. The optical feedback parameters C and <semantics>α</semantics> in the strong feedback regime (<semantics>C≥4.6</semantics>) are estimated from the SMI vibrometric signals and by the solving of non-linear equations governing the SMI behaviour. The calibration method is validated on synthetic SMI signals simulated from SMI governing equations for C ranging from 5 to 20 and <semantics>α</semantics> ranging from 4 to 10. Knowing C and <semantics>α</semantics>, the SMI is then used as an acoustic pressure sensor. The SPLs obtained using the SMI are compared with a reference microphone, and a maximal deviation of 2.2 dB is obtained for plane waves of amplitudes ranging from 20 to 860 Pa and frequencies from 614 to 17,900 Hz. The SPL measurements are carried out for C values ranging from 7.1 to 21.5.